1995
DOI: 10.1289/ehp.95103s7165
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive effects in birds exposed to pesticides and industrial chemicals.

Abstract: Environmental contamination by agricultural chemicals and industrial waste disposal results in adverse effects on reproduction of exposed birds. The diversity of pollutants results in physiological effects at several levels, including direct effects on breeding adults as well as developmental effects on embryos. The effects on embryos include mortality or reduced hatchability, failure of chicks to thrive (wasting syndrome), and teratological effects producing skeletal abnormalities and impaired differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(117 citation statements)
references
References 58 publications
2
112
0
3
Order By: Relevance
“…As in Table 1, there is a clear distinction between adult females (specimens 1, 5, and 12), for which 100 to 1000 copies of Vg mRNA were obtained per copy of β-actin mRNA, and adult males or juveniles, some specimens of which (2, 3, and 4) gave no specific amplification products or very low copy values, less than 1/1000 of the levels for adult females (specimens 9, 10, and 11). However, some males (13,14) and juveniles (6,7,8) contained significant levels of Vg mRNA, similar to those found in F. heteroclitus males treated with NP (Table 1). Although anatomical and histological examination of these specimens are still in progress, previous work on carp from the same area detected the presence of intersexes (i.e.…”
Section: Detection Of Vg Mrna In Feral Fishessupporting
confidence: 76%
See 1 more Smart Citation
“…As in Table 1, there is a clear distinction between adult females (specimens 1, 5, and 12), for which 100 to 1000 copies of Vg mRNA were obtained per copy of β-actin mRNA, and adult males or juveniles, some specimens of which (2, 3, and 4) gave no specific amplification products or very low copy values, less than 1/1000 of the levels for adult females (specimens 9, 10, and 11). However, some males (13,14) and juveniles (6,7,8) contained significant levels of Vg mRNA, similar to those found in F. heteroclitus males treated with NP (Table 1). Although anatomical and histological examination of these specimens are still in progress, previous work on carp from the same area detected the presence of intersexes (i.e.…”
Section: Detection Of Vg Mrna In Feral Fishessupporting
confidence: 76%
“…Some of the main sources of endocrinedisrupting compounds (EDC) include tannery effluents, paper and pulp mill effluents, crude oil derivatives, and sewage effluents. In the past few years numerous effects of these EDC have emerged, including intersex of river fish, and reproductive failure and abnormalities in marine vertebrates [2,3], birds [4,5,6], alligators [7,8], and polar bears [9]. It has, for instance, been demonstrated that several STP effluents in the UK are estrogenic to fish [10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The causes of the impaired hatching success and elevated mortality of male embryos remain unclear, and only very few similar examples of skewed population sex ratios have been reported (Fry et al 1987;Hunt and Hunt 1977). Impaired reproductive success in birds has in some cases been suggested to result from exposure to environmental contaminants in the form of agricultural chemicals or industrial waste (Fry 1995;Vos et al 2000). There is, however, one previously reported sample of a Californian population of Western Gulls, breeding in an area heavily polluted by organochlorine compounds, where the population sex ratio appeared to be significantly female biased (Hunt and Hunt 1977;Fry and Toone 1981;Fry et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Light pollution can also affect bird behaviour by advancing avian singing time at dawn and dusk (Da Silva et al, 2014). Finally, the increased exposure to environmental toxic chemicals-chemical pollution-can affect birds' physiology and phenotype directly but also indirectly because of habitat alterations or parasites spread (Morrison, 1986;Eeva et al, 1994;Fry, 1995;Isaksson, 2015).…”
Section: Introductionmentioning
confidence: 99%